An Empirical Study: The effect of Supply Chain Management Practices towards Competitive Advantage and Business Performance. - Sutanto, J.E.Sutanto; Kodrat, David Sukardi (International Journal of Supply Chain Management, 2020)
Purpose, to achieve efficiency and effective supply chain management (SCM) has become a potential to increase competitive advantage and improve business performance. Design/methodology/approach, in this research process the respondents as sample size is 125 and the data processing used program SmartPLS. Findings, it can be concluded that, first, supply chain management practices have a positive and significant impact on business performance; second, supply chain management practices have a positive and significant impact on competitive advantage; third, competitive advantage has an impact on business performance. Originality/value, first, the results of the study are used as a reference or new literature, and second, research  results will be useful for academics, and researchersKeywords: Supply chain management practices, Competitive advantage, Business performance,